Auditoria Forense como la mejor herramienta para la detección de operaciones de fraude financiero en las empresas de servicios. - Ayala Dávila, Lenin Rubén (2014)
Forensic Auditing audit work is one that focuses on the prevention and detection of financial fraud, which is why generally the results of work of the Forensic Auditor are made consideration of justice, to take charge of analyzing, judging and sentencing offenses committed (financial, public or private corruption). To develop the present research, was selected NEIPOL SAC, which was submitted to the research design, analysis focusing on unusual and suspicious transactions and business transactions conducted during 2011 and 2012. Investigation and analysis concludes that NEIPOL SAC, does not have a good control of emergency cash and is implementing an internal control system, which would help to eliminate or minimize the risk of possible fraud against the company. It is proposed that the forensic audit by its different from the traditional audit approach provides methods needed to address and identify with a high degree of efficiency possible unusual and suspicious transactions that attempt to engage in technical NEIPOL SAC.